PENGARUH STRATEGI PEMASARAN TERHADAP VOLUME PENJUALAN PADA PT. RUSDI MEDIKA - Luh Kadek Budi Martini; A.A Istri Ngr. Dyah Prami; Kadek Yashinta Viediantari (Journal of Applied Management Studies, 2022)
The title of the research on the influence of marketing strategy on sales volume at PT. Rusdi Medika. To carry out marketing activities, it must be supported by a marketing strategy commonly referred to as the "4P" namely product, price, distribution and promotion which are important factors in marketing intangible and tangible products. The purpose of this study was to determine the effect of marketing strategy on sales volume at PT. Rusdi Medika. The population in this study are customers or customers of PT. Rusdi Medika in 2021. The sample of this study was 100 respondents. The sampling technique used in this research is using the slovin formula. Sources of data used are primary and secondary data. Data analysis using SPSS for Windows version 25. The data collection procedure in this study used interview, documentation and questionnaire techniques using a Likert scale. The data analysis technique used multiple linear regression analysis. The results obtained from statistical analysis showed that the magnitude of the influence of marketing strategy on sales volume at PT. Rusdi Medika is 52.5% with hypothesis testing using t-test, with the result that the product variable (X1) has a positive and significant effect with the t-count result of 2.774 with sig 0.007 of the sales volume variable (Y). The price variable (X2) has a positive and significant effect with the t-count result of 2.563 with a sig of 0.005 on the sales volume variable. The distribution variable (X3) has a positive and significant effect with the t-count result of 2.317 with a sig of 0.023 on the sales volume variable. The promotion variable (X4) has a positive and significant effect with t-count of 2,920 and sig of 0.004 on the sales volume variable.